2012
DOI: 10.12693/aphyspola.122.561
|View full text |Cite
|
Sign up to set email alerts
|

Basic Electrochemical Behavior of Ti-7Cu Alloys for Medical Applications

Abstract: The aim of this study was to investigate the e ects of two di erent treatments, as-cast setup and solution heat treatment, on the general electrochemical corrosion resistance of Ti 7Cu alloy samples immersed in a 0.9 wt% NaCl solution at 25 • C. The microstructure was examined by scanning electron microscopy and X-ray di ractometry. Corrosion behavior was tested by potentiodynamic polarization curves. Finer α ′ martensite and Ti2Cu intermetallic particles were provided by casting and heat treated processes, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Recently, very similar I pp measurements have also been obtained for Ti 7 Cu alloys [13,22]. Although a strongly protective Ti oxide film forms on the surface of such samples, the high values of I pp suggest that this oxide can be more defective or porous, which can be helpful to the osseointegration process.…”
Section: Potentiodynamic Polarizationmentioning
confidence: 54%
See 2 more Smart Citations
“…Recently, very similar I pp measurements have also been obtained for Ti 7 Cu alloys [13,22]. Although a strongly protective Ti oxide film forms on the surface of such samples, the high values of I pp suggest that this oxide can be more defective or porous, which can be helpful to the osseointegration process.…”
Section: Potentiodynamic Polarizationmentioning
confidence: 54%
“…So, it has incorporated into the surface of a variety of biomaterials [9,10]. Another, many attempts have been made to develop new Ti-Cu system alloys to achieve better performance [11][12][13][14][15][16][17][18][19][20]. Investigations by Kikuchi et al have shown that Ti-Cu alloys may offer very high mechanical strength associated with good formability [11] and a comparatively lower melting temperature [11,12], which makes it applicable to dental casting processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have excellent properties, such as high specific strength, good formability, corrosion resistance, non-toxicity, and excellent biocompatibility [1], [2]. New titanium alloys for biomaterials such as Ti-Nb [3], Ti-Cu [4], Ti-Cu-Sn [5] have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium and its alloys are widely used because of their interesting properties, especially their excellent corrosion resistance due to high chemical inertness, combined with low density compared to steel [1][2][3][4][5][6]. Applications of titanium alloys in the medical field as implants or prostheses among other uses [7][8][9][10][11][12] led to define for the purposes of research, simulated biological media to the human body with concentrations equal to that of ions, like blood plasma.…”
Section: Introductionmentioning
confidence: 99%